ANXIETY IN STUDENTS’ PHONOLOGICAL AND GRAMMATICAL ARABIC LEARNING AT MTS NU 19 PROTOMULYO - Afgani, Rahardian Al; Inayah, Inayah; Abu Samra, Asma’ Naim Jamil; Aini, Tuti Qurrotul (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
This study examines the forms, causes, and impacts of student anxiety in learning Arabic phonology and grammar at MTs NU 19 Protomulyo. Employing a descriptive qualitative approach with limited quantitative support, the research utilizes classroom observations, semi-structured interviews, document analysis, and an adapted Foreign Language Classroom Anxiety Scale (FLCAS). Participants were purposively selected, focusing on students exhibiting linguistic anxiety, with the Arabic teacher serving as a key informant. Findings indicate that students experience communication apprehension, test anxiety, and fear of negative evaluation, particularly in pronunciation and grammatical usage (nahwu-ṣharaf). These anxieties stem from low self-confidence, assessment pressure, and classroom social dynamics, which together reduce participation and comprehension. The study underscores the need for effective supportive teaching strategies to improve Arabic language learning